Methodology For Using Computer Training Programs In English Lessons - et. al., Aziza Zikiryaevna Shodikulova, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
One Of The Most Important Issues Today Is The Creation Of New, Modern Pedagogical Technologies In The Teaching Of Language To Students, Their Application In Practice. This Scientific Article Provides Detailed Information On Methodology Of Computer Training Program In Teaching A Foreign Language In A School. It Also Provides Examples And Clear Analysis Of How Important It Is To Apply This Method To Life. Features Of Programs In Accordance With The Possibilities Of Foreign Language Education In Primary School, Teaching Computer Programs For School In Flt And The Role Of Cp In Organization Of Foreign Language Lessons Will Be Solved Depending On The Purpose Of The Article. The Subject Of The Research Is Expressed By Multimedia Programs As A Means Of Teaching English.